A novel pneumatic separator for separating diode and CD capacitance of waste printed circuit boards. (1st January 2018) - Ruan, Jujun; Huang, Zhe; Huang, Jiaxin; Yuan, Zhihui; Huang, Mingzhi; Du, Changming; Zhang, Tao; Qiu, Rongliang
Abstract: Waste printed circuit boards (WPCBs) contain abundant metals. Recovering WPCBs is significant in energy conservation, sustainable development, and environmental protection, which save the energy and environment cost of searching and melting of metals. Many reports were related to environment-friendly disposal of basal boards of WPCBs. Little information was reported about the recovery technology of electronic components. In this paper, a novel and pollution-free pneumatic separator was invented to separate diode (Ti enriched components) and CD capacitance (Sn enriched components). Trajectory models of diode and CD capacitance in pneumatic separation were established. Then, optimized parameters of airflow velocity (0.77 m/s) and position (0.16 m) of separation plate of pneumatic separation were obtained. Separation rates of diode and CD capacitances in pneumatic separation reached up to 96.7 wt% and 97.3 wt%. This paper provided an environment-friendly and high-efficiency separator for separating electronic components of WPCBs. The trajectory models also can guide pneumatic separation of other electronic components. Graphical abstract: Image Highlights: Recovering e-waste is significant in energy conservation, sustainable development, and environmental protection. Little information was reported about recovery technology of electronic components of WPCBs. New pneumatic separator was designed to separate different electronic components of WPCBs.